An integrative approach challenges species hypotheses and provides hints for evolutionary history of two Mediterranean freshwater palaemonid shrimps (Decapoda: Caridea). Issue 1 (1st January 2021) - Jabłońska, A.; Navarro, N.; Laffont, R.; Wattier, R.; Pešić, V.; Zawal, A.; Vukić, J.; Grabowski, M.
Abstract: The Mediterranean Region is a biodiversity/endemism hotspot whose freshwater fauna remains largely unexplored. Our integrative study challenges the taxonomic status of two freshwater palaemonid shrimps, Palaemon antennarius and Palaemon minos . Three molecular operational taxonomic units (MOTUs) were defined based on 352 cytochrome oxidase subunit I (COI) sequences and 88 haplotypes. Two belonged to P. antennarius : one inhabiting the Apennine Peninsula and Sicily, and the other from the Balkan Peninsula. Palaemon minos was the third MOTU, found on Crete. The Balkan MOTU of P. antennarius was genetically closer to P. minos than to the other conspecific MOTU. Data from a nuclear marker (Histone 3) is congruent with such a pattern. The carapace shape variation (based on 180 individuals) was mainly explained by the geographical distribution. Balkan and Cretan groups were clearly recovered, while other samples clustered along a shape gradient from Sicily, through the Apennine Peninsula to the Balkans. Our results show that, for taxonomic consistency, the MOTU inhabiting the Balkan Peninsula should be either described as a new separate species or synonymised with P. minos . The third possible option would be treating all the populations as part of P. antennarius . Geometric morphometrics supports the first option, phylogenetic reconstructions point to the second one, yet the low genetic divergence favours the third one, illustrating that even emblematic taxa such as shrimps require an in-depth integrative approach.